2021
DOI: 10.1186/s13007-021-00730-9
|View full text |Cite
|
Sign up to set email alerts
|

A label-free, fast and high-specificity technique for plant cell wall imaging and composition analysis

Abstract: Background New cell wall imaging tools permit direct visualization of the molecular architecture of cell walls and provide detailed chemical information on wall polymers, which will aid efforts to use these polymers in multiple applications; however, detailed imaging and quantification of the native composition and architecture in the cell wall remains challenging. Results Here, we describe a label-free imaging technology, coherent Raman scattering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Advancing cell wall analytical methods provide promising prospects, with a growing demand for high-throughput methods for rapid screening and profiling of cell wall components ( Persson et al , 2011 ). Spectroscopic methods have been widely used for cell wall characterization ( Bauer, 2012 ; Mansfield et al , 2012 ; Pettolino et al , 2012 ; Gierlinger, 2018 ; Zhao et al , 2020 ) in combination with imaging techniques ( Zhao et al , 2019 ; Bidhendi et al , 2020 ; DeVree et al , 2021 ; Xu et al , 2021 ). Recent advances in non-destructive real-time imaging, such as light-sheet fluorescence microscopy (LSFM), could allow us to observe changes in the cell walls of succulent tissues under drought in near-physiological conditions ( Grossmann et al , 2018 ; Ovečka et al , 2018 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Advancing cell wall analytical methods provide promising prospects, with a growing demand for high-throughput methods for rapid screening and profiling of cell wall components ( Persson et al , 2011 ). Spectroscopic methods have been widely used for cell wall characterization ( Bauer, 2012 ; Mansfield et al , 2012 ; Pettolino et al , 2012 ; Gierlinger, 2018 ; Zhao et al , 2020 ) in combination with imaging techniques ( Zhao et al , 2019 ; Bidhendi et al , 2020 ; DeVree et al , 2021 ; Xu et al , 2021 ). Recent advances in non-destructive real-time imaging, such as light-sheet fluorescence microscopy (LSFM), could allow us to observe changes in the cell walls of succulent tissues under drought in near-physiological conditions ( Grossmann et al , 2018 ; Ovečka et al , 2018 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The obtained SRS images were processed for analysis using Fiji software, as described by Xu et al [15]. Briefly, images were opened and changed to 8 bit.…”
Section: Quantitative Analysis Of Srs Imagementioning
confidence: 99%
“…In order to compare the lignin deposition between the two cultivars, the mature xylems of both cultivars were observed under SRS microscopy and images were acquired at 1600 cm −1 . Subsequently, a quantitative and straightforward SRS image analysis was made, as described by Xu et al [15]. SRS imaging showed that lignin concentrations in the cell corner and compound middle lamella were higher than those in the secondary cell wall.…”
Section: Differences Of Lignin and Cellulose Deposition In Matured Xy...mentioning
confidence: 99%
See 2 more Smart Citations